Mechanistic study of the bioactivity improvement of Al2O3-doped BBG after dynamic flow treatment. Issue 1 (1st January 2023) - Chen, Ruiguo; Sun, Lei; Tan, Renhao; Xu, Shuai; Xu, Huangtao; Zhao, Xianglong; Tao, Tongxiang; Zhang, Qi; Xia, Haining; Han, Jian; Liu, Chao; Yu, Zhiwu; et al.
Abstract: A simple and effective method for improving the biological activity of borate bioactive glass (BBG) is to perform dynamic flow treatment with simulated body fluid (SBF). The phosphate layer formed on the BBG surface during flow treatment enhances the biocompatibility of this bioglass. However, the micromechanism of the formation of highly bioactive mineralized products on the surface of BBG under dynamic flow treatment is not clearly understood. In this study, we investigated the effect of dynamic flow treatment on the biological properties of Al2 O3 -doped BBG. The results revealed that the SBF-treated Al2 O3 -doped BBG exhibits significantly reduced degradation rate and improved bioactivity. The characterization of the treated Al2 O3 -doped BBG by Fourier-transform infrared and solid-state NMR spectroscopies revealed that Al mainly exists in the form of four-coordinated aluminum in BBG. During the dynamic flow treatment process, four-coordinated aluminum transforms into six-coordinated aluminum, which chemically interacts with PO4 3− to improve the biological activity of Al-BBG. In addition, the much more phosphate deposited on BBG sample containing less Al2 O3 and promote hydroxyapatite formation on the glass surface. In vitro cell studies suggested that the Al2 O3 -doped BBG after treated by dynamic flow treatment boosts the proliferation of MC-3T3E1. This work demonstrates that dynamic flow treatment is a simple and effective method for improving the bioactivity of BBG and also expands our understanding of the micromechanics of the degradation and biomineralization of Al2 O3 -doped BBG.